(untitled) (Libellarium: journal for research in the field of information and related sciences, 2011)
The aim of the paper is to analyse the actual status of book publishing in Croatia, envisage the trends of its future development and, by analyzing the current state of affairs and new book marketing trends, draw conclusions as to which directions the publishing companies should take in order to survive on the market. The aims stated as such result from the author’s research and review of the business operations of the ‘Naklada Ljevak’ publishing company, and from the monitoring of relevant home and foreign literature in the field of marketing in general as well as specialized book marketing literature. In the introductory part the author defines publishing and its amphibious nature that lies in the fact that publishing is at the same time the process of creation and distribution of knowledge and culture, as well as a business resulting in education, as well as in entertainment. The following chapter offers an explanation of the most important facts required to understand the current publishing marketing (globalization, huge sales chains, fierce competition, ever lower standard of living in Croatia…) and lists the marketing programme elements applicable to publishing. Further on, the focus shifts on the book as a product and a part of publishing marketing. It mentions the economic and business trends that have affected the development of publishing as an industry over the past sixty years, and the book as a product. New book content trends have been elaborated as well: novels on exotic countries, current affairs issues, autobiographies and biographies, self-help manuals and titles offering ‘instant-knowledge’. There is a definition and explanation of trends that relate to the book as a material product such as cover design, format, binding, types of print paper and technical features such as layout, margins, font size and spacing.